"How did I get this lucky?" : issues of power, intimacy and sexuality in the construction of young women's identities within their heterosexual relationships - McEwen, Caryn (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2006)
This thesis seeks to explore how young, educated and seemingly liberated women construct their identities and make sense of their futures around their heterosexual relationships. Using the experiences of eight women participants engaged in long-term heterosexual relationships, combined with relevant secondary literature, issues of sexuality, identity, power and intimacy are discussed. Emphasis is placed on the implications of their identity construction and how they 'perform' their roles as women in society. How their sexual stories reflect their positioning in society is premised by the phrase, 'the personal is political' . Through analysis of the participants' experiences mixed with theoretical arguments, this thesis finds that young women are apparently sexually, economically and intellectually liberated but locked into discourses that provide highly unequal, limiting, disempowering and oppressive understandings of masculinity, femininity and sexuality. They live and experience a reality which is far from liberated.
Keywords: Foucault, Michel, 1926-1984 -- Criticism and interpretation; Heterosexuality; Heterosexual women; Women -- Sexual behavior; Feminism -- Political aspects; Sex role -- Political aspects; Feminist psychology; Sex (Psychology)